The effects of Angiotensin-converting-enzyme inhibitor (Enalapril) on gentamicin nephrotoxicity - Al-Ani, Imad Matloub Dally; Nafie, Emad M.; Algantri, Khaled R. (2014)
Gentamicin (GM) is one of Aminoglycosides widely used for the treatment of serious gram negative infections. Many risk factors associated with aminoglycosides nephrotoxicity have been identified in human and experimental animals. Enalapril is one of Angiotensin converting enzyme inhibitors (ACEI) which is widely used for the treatment of hypertension and heart failure. It has been suggested that (ACEI) may increase or decrease the nephrotoxicity of Aminoglycosides. The present study was undertaken to evaluate the concomitant administration of Enalapril and Gentamicin. Sixty healthy adult male Sprague Dawley rats were divided into four major groups of 15 rats each (according to the dosage of administered drug). Each major group was further subdivided into three minor groups according to the sacrificing day. Group (C) = control group were administered daily with normal saline, group (G) were given 75 mg/kg GM, group (E) were given oral enalapril and group (G + E) were GM and enalapril. Treatment continued daily for 15 days and experimental analysis has been done on day 5, 10 and 15. It has been found that GN nephrotoxicity increased with the duration of treatment through elevation of serum creatinine and blood urea nitrogen at the 10th day and continued to increase significantly throughout the experiment at the 15th day. Animals treated with Enalapril showed no significant alteration from those of controls, while the concomitant administration of Enalapril and GM revealed that Enalapril progressively aggravated GN nephrotoxicity, these physiological alterations were associated with severe renal histopathological changes induced by GM.